A bibliometric and visualized analysis of heartland virus - Huiying Zhang; Huiying Zhang; Leiliang Zhang; Leiliang Zhang (Frontiers in Microbiology)
BackgroundHeartland virus (HRTV) is an emerging tick-borne bunyavirus first detected in 2009. The purpose of this study was to utilize bibliometric analysis to assess the research trends, key foci, and progress of HRTV. This analysis aims to provide valuable references and insights for future basic research and prevention and control of HRTV to promote the progress and development of related fields.MethodsThe Web of Science Core Collection (WOSCC) was used to extract global publications on the HRTV from 2013 to 2024. VOSviewer, CiteSpace, Scimago Graphica, and Bibliometrix were used to process the data and visualize the results.ResultsA stable trend in publication numbers was observed, with 82 articles from 17 countries. The United States led in publications, with significant contributions from the Centers for Disease Control and Prevention-USA. Keywords indicated research emphasis on “Heartland virus” and “severe fever.”ConclusionHRTV research is in a phase of continuous and progressive growth, with a steady literature output over the past decade, indicating this field’s wide interest and importance in the research community. Currently, researchers are focusing on pathogenesis, immune response, vector relationships, and epidemiology, providing valuable insights for future studies.